Enhancing aero engine performance through synergistic combinations of advanced technologies. - Rolt, Andrew Martin (Cranfield University, 2019)
By 2050 the evolutionary approach to aero engine research and development will no longer be able to maintain historic rates of performance improvement. Future geared fan and open rotor engines promise increased propulsive efficiency and reduced noise, but will need to incorporate new technologies to improve core thermal efficiency in order to meet the ambitious fuel-burn and emissions targets set by ACARE in Flightpath 2050. In the face of increasing air traffic, radical new approaches will be needed to minimize the impact of aviation on the environment. A long-term vision is required. This PhD project investigates the potential of innovative propulsion technologies for civil aviation. Candidate technologies include topping and bottoming cycles, secondary combustion, intercooling and recuperation. The reported research investigates potential synergies between these advanced core technologies that when integrated together should give a significant fuel burn reduction relative to a more-conventional year-2050 ‘reference’ Brayton-cycle turbofan. Spreadsheet models have been used to quantify performance and estimate the weight and fuel burn savings for each new engine cycle. Further models were created to investigate preferred topping and bottoming cycle arrangements. NOx emissions are estimated for engines with rich-quench-lean (RQL) or lean-direct-injection (LDI) combustors. The correlation for future LDI combustor NOx emissions was selected following a review of recent LDI combustor research and a detailed study of alternative options. Increasingly aerodynamically efficient and lighter weight aircraft with more efficient engines will have lower thrust requirements. Advanced engine cycles also generally increase core specific power and reduce core mass flow, so future engines will have smaller turbo-machines that will tend to have lower component efficiencies. Therefore a preliminary study investigated the effects of thrust-scaling on the efficiency of the reference turbofan and possible high-OPR intercooled engines, since these could have very small core components. Novel core-component designs and engine architectures can minimize these penalties. Positive-displacement topping-cycle machines and reverse-flow-core engine layouts should help to maintain component efficiency and improve SFC, but low weight and low drag are also essential to minimize fuel burn. Therefore weight assessments of the advanced engine designs were made, and fuel-burn exchange rates used to quantify expected mission-level CO₂ reductions. Following a qualitative assessment of synergies between potential advanced technologies, an engine that combines intercooling, a topping cycle, secondary combustion and an open-air-cycle bottoming cycle was selected for detailed study. While each of these technologies has been researched previously, the contribution and value that each advanced core technology could bring to the whole in a large geared turbofan has not so far been reported. The approach initiated was to model a series of engines omitting each technology in turn and this scheme has been partially realized. The modelled topping-cycle technology uses six nutating-disc modules as a replacement for conventional combustors, high pressure compressors and turbines. A nutating-disc core module concept design led to the creation of a display model that was shown on the ULTIMATE project stand at the 2018 Farnborough International Air Show. The selected cycle combining all four technologies should reduce SFC by about 15% relative to the reference year-2050 turbofan and is assessed to reduce fuel burn by up to 18.5% in a long-range aircraft. An engine with intercooling, intra-turbine combustion and a bottoming cycle reduces SFC by about 6%, and an engine that is simply intercooled reduces SFC by about 3%. The topping cycle gives the biggest potential thermal efficiency improvement, but nutating-disc technology presents very significant design challenges for large aero engines, particularly with regard to internal sealing and bearing loads. Therefore it is recommended that alternative topping-cycle technologies should be researched for long-term aero engine performance improvements. A further study shows the effect of the target 15% reduction in fuel burn on in-flight CO2 emissions by the civil aviation fleet under various traffic-growth scenarios.
Keywords: topping cycles; Propulsion technologies; bottoming cycles; secondary cycles; secondary combustion; intercooling; recuperation